2019
DOI: 10.1152/ajplung.00335.2018
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of A20 (TNFAIP3): new drug-able targets in inflammation

Abstract: Persistent activation of the transcription factor Nuclear factor-κB (NF-κB) is central to the pathogenesis of many inflammatory disorders, including those of the lung such as cystic fibrosis (CF), asthma, and chronic obstructive pulmonary disease (COPD). Despite recent advances in treatment, management of the inflammatory component of these diseases still remains suboptimal. A20 is an endogenous negative regulator of NF-κB signaling, which has been widely described in several autoimmune and inflammatory disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 144 publications
2
36
0
Order By: Relevance
“…We have highlighted in navy blue the expression of EGR3 and TWIST1, the two genes whose differential expression presents the largest fold changes in cluster B. TWIST1 negatively regulates the NF-κB protein complex. TWIST1 is thus anti-inflammatory [24]. The variation in the TWIST1 time series in Error!…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have highlighted in navy blue the expression of EGR3 and TWIST1, the two genes whose differential expression presents the largest fold changes in cluster B. TWIST1 negatively regulates the NF-κB protein complex. TWIST1 is thus anti-inflammatory [24]. The variation in the TWIST1 time series in Error!…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 5, bottom-left panel (olive green) highlights the differential expression evolution of JUN and TNFAIP3 from cluster B. JUN encodes c-Jun, a protein that participates in the transcription-factor complex "Activator Protein-1" (AP-1) that has complex context-dependent behaviors [22]. In epithelial cells AP-1 components (containing c-Jun) may participate in apoptosis or cell proliferation.…”
Section: Fig 5 Time Evolution For the Differential Expression Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased appreciation of ubiquitin-mediated regulation of key biological processes in health and disease states has led to the discovery of A20 as a critical modulator of cellular homeostasis (Hu and Sun 2016; Malynn and Ma 2019; Martens and van Loo 2020; Priem et al 2020). Genome-wide association studies identified somatic mutations, deletions, and/or aberrant expression of A20 in rheumatoid arthritis, diabetes, SLE, inflammatory bowel disease, psoriasis, Sjögren syndrome, coronary artery disease, multiple sclerosis, cystic fibrosis, and asthma (Boonyasrisawat et al 2007; Ma and Malynn 2012; Momtazi et al 2019; Martens and van Loo 2020). While A20 function is fairly well-characterized in several tissues, only recently did it begin to receive attention as a regulator of oral mucosa homeostasis.…”
Section: Insights For A20 Function In the Oral Cavitymentioning
confidence: 99%
“…In addition, aberrant function of enzymes involved in ubiquitin regulation oftentimes contribute to the onset and progression of several disorders. Particularly, abnormal expression and/or function of ubiquitin-editing protein A20 (tumor necrosis factor α–induced protein 3 or TNFAIP3) has been associated with chronic inflammation and tissue damage, contributing to the immunopathology of multiple human autoimmune and inflammatory diseases, including diabetes and cancer, as well as pulmonary, neurological, skin, and gastrointestinal disorders (Fukaya et al 2016; Zhou et al 2016; Aeschlimann et al 2018; Kadowaki et al 2018; Devos et al 2019; Momtazi et al 2019). Recent evidence also reveals the ubiquitin system and A20 as a critical regulator in the oral cavity and particularly in periodontal disease pathogenesis (Hong et al 2016; Zhou et al 2016; Crump et al 2017; Li et al 2019; 2020; Yan et al 2020).…”
Section: Introductionmentioning
confidence: 99%